Network pharmacology combined with experimental verification for exploring the potential mechanism of phellodendrine against depression - Lili Hu; Na Wu; Jue Wang; Donghui Cai (Scientific Reports)
Abstract The anti-inflammatory effect of phellodendrine (PHE), derived from Phellodendri Chinensis Cortex, has been verified in previous studies. Major depressive disorder (MDD) is associated with immune dysregulation and inflammatory processes. This study aimed to explore the therapeutic effects of PHE on MDD through network pharmacology and experimental validation. Multiple databases were used to predict the targets of PHE and MDD. The intersection targets between PHE and MDD were obtained to identify as targets for PHE against MDD, followed by protein–protein interaction network, Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway analyses. Molecular docking was applied to further confirm the anti-MDD effects of PHE. The mitochondrial DNA (mtDNA) copy number, inflammatory cytokines and pathway-related mRNA expressions in PC12 cell were determined via quantitative PCR (qPCR) and enzyme-linked immunosorbent assay to verify our finding. Thirty-eight intersection targets were obtained between PHE and MDD. PHE exerted an anti-MDD effect by regulating SLC6A4, SLC6A3, SLC6A2, MAOA and other targets through serotonergic synapse, salivary secretion, dopaminergic synapse, and cAMP signalling pathway. In vitro, PHE induced an increment in mtDNA copy number compared with the CORT group. PHE affected the levels of IL6 and IL1β with different concentrations. The mRNA levels of CHRM1, HTR1A and key targets of the PI3K/Akt signalling pathway were also influenced. Our research reveals novel mechanisms underlying the anti-MDD effects of PHE through network pharmacology and experiments, which provides a new direction for the development of antidepressants.